The Role of Novelty in Securing Investors for Equity Crowdfunding Campaigns - Horvát, Emőke-Ágnes; Wachs, Johannes; Wang, Rong; Hannák, Anikó (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2018)
In recent years crowdfunding has diversified and grown beyond most experts’ projections. Originally aiming to serve venture ideas and entrepreneurs outside the focus of traditional capital markets, the crowdfunding marketplace has developed a complicated relationship with novel ideas. Yet, there is little to no research on the relationship between project novelty and success in crowdfunding. This paper measures the novelty of crowdfunding campaigns using the content and language of their pitches, capturing their tendency to combine different venture sectors and topics in distinctive ways. Using a unique data set that covers four years of activity on a leading equity crowdfunding platform, we investigate the link between novelty and success, as well as how novelty appeals to different kinds of investors. We find that novelty derived from campaign pitches is negatively related with fundraising success even when controlling for quality and style of writing. We also find that novel campaigns are more likely to attract less-frequent, large-sum investors. Our findings contribute to the long-standing debate related to the trade-offs between innovativeness and conventionality in maximizing chances of startup survival. Our results also have important implications for entrepreneurs writing fundraising pitches and for platform providers who wish to facilitate successful innovation.